Evaluation of Zinc, Iron and Selected Trace Element (Magnesium, Phosphorus, Calcium) In Short Stature Child in Wassit Province (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Short stature affects over 25% of children under 5 worldwide. It frequently results from chronic malnutrition and micronutrient deficiencies. This study aimed to assess the status of zinc, iron, and selected trace elements in children with short stature in Wasit, Iraq where stunting prevalence is high.Methods: This cross-sectional study included 50 children with short stature (height-for-age z-score < -2) and 50 controls (height-for-age z-score > -1), aged 3-13 years in Wasit, Iraq. Serum zinc, iron, ferritin, magnesium, phosphorus and calcium were measured. Dietary intake was assessed by food frequency questionnaire. Growth parameters were determined by anthropometry.Results: Short stature children had significantly lower serum zinc and iron compared to controls. Zinc deficiency (